2000
DOI: 10.1046/j.1365-3059.2000.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in host range, pathogenicity to potato cultivars and response to soil temperature among Streptomyces species causing common and netted scab in France

Abstract: The pathogenicity and ecology of some isolates representative of the four main Streptomyces species (S. scabies, S. europaeiscabiei, S. stelliscabiei and S. reticuliscabiei) identified as pathogenic to potato tubers were investigated. Three pathogenicity groups could be distinguished. Group 1 included all isolates of S. scabies, S. europaeiscabiei and S. stelliscabiei from common scab lesions of potato and other susceptible root crops. All these produced similar symptoms and were pathogenic to potato, carrot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…from Venezuelan soils. Isolates from netted scab in the Netherlands were positive for melanin production, and considered identical to S. scabiei (Bouchek-Mechiche et al 2000). Netted scab isolates that did not produce melanin were however also reported from Denmark and Sweden.…”
Section: Discussionmentioning
confidence: 98%
“…from Venezuelan soils. Isolates from netted scab in the Netherlands were positive for melanin production, and considered identical to S. scabiei (Bouchek-Mechiche et al 2000). Netted scab isolates that did not produce melanin were however also reported from Denmark and Sweden.…”
Section: Discussionmentioning
confidence: 98%
“…Finnish netted scab pathogen was also classified as S. aureofaciens (Kreuze et al 1999). Netted scab in France was induced by S. reticuliscabiei and some strains of S. europaeiscabiei (Bouchek-Mechiche et al 2000a, 2000b. S. reticuliscabiei and S. europaeiscabiei are closely related to S. turgidiscabies and S. scabies, respectively; and S. aureofaciens is distantly related to these species in 16S rRNA analysis (Song et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Common scab symptoms consist of superficial to deep corky lesions on the tubers. Methods used to control common scab include chemical treatments of seed potato tubers (Davis et al, 1976), irrigation (Adams and Lapwood, 1978), rotation strategies (Li et al, 1999), use of a tolerant cultivar (Bouchek-Mechiche et al, 2000), soil amendment with chitinous compounds (Vruggink, 1970;Beause´jour et al, 2003) and biological control with non-pathogenic streptomycetes (Liu et al, 1995;Ryan and Kinkel, 1997;Doumbou et al, 1998;Agbessi et al, 2003;Beause´jour et al, 2003). Recently, Beause´jour et al (2003) reported the use of a biological agent (Streptomyces melanosporofaciens Arcamone et al strain in combination with chitosan to control common scab.…”
Section: Introductionmentioning
confidence: 99%